1968
DOI: 10.1111/j.1445-2197.1971.tb05193.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume in Malignant Disease: Case Studies in 86 Females1

Abstract: The problem of blood replacement in the individual cancer patient remains unanswered. On present evidence, such a patient must be assumed to be drawn from a population with a mean total blood volume and mean red-cell volume below normal and thus must be assumed to have a better-than-even chance of having a depleted volume. However, it does not necessarily follow that transfusion is necessary; this should ideally be assessed by blood volume determination in each individual case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
1971
1971

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…(3) The mean F.C.R. in control animals was in good agreement with previously reported values in rabbits (Reeve and Roberts, 1959;Matthews, 1965) and in rats (Matthews, 1957). In rabbits mean results on four occasions were 025, 021, 026 and 0225 calculated both by the U/P method and by compartmental analysis.…”
Section: Npsupporting
confidence: 89%
See 1 more Smart Citation
“…(3) The mean F.C.R. in control animals was in good agreement with previously reported values in rabbits (Reeve and Roberts, 1959;Matthews, 1965) and in rats (Matthews, 1957). In rabbits mean results on four occasions were 025, 021, 026 and 0225 calculated both by the U/P method and by compartmental analysis.…”
Section: Npsupporting
confidence: 89%
“…However, these findings were not confirmed by Reeve et al (1968). Peden et al (1960) showed that the amount of body fat was a significant factor and that quite high plasma volumes per unit body weight were found in cases of non malignant cachexia.…”
Section: Resultsmentioning
confidence: 86%